Thermal renovation of buildings with the use of straw - European experience = Termorenowacja budynków z użyciem słomy - doświadczenia europejskie - Golański, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The selection of building materials to a huge extent shapes building impact on the environment. In the era of widespread awareness of health problems arising from toxicity of chemical substances, healthy and safe materials of organic origin are even more important. The work discusses examples of the use of straw-bales in thermal retrofitting of buildings located in Austria, Czech Republic and Hungary.
Keywords: natural building materials; thermorenovation; ecological homes; straw-clay walls; naturalne materiały budowlane; termorenowacja; domy ekologiczne; budownictwo z gliny; budownictwo ze słomy